The game of silence ebook - Erdrich, Louise (The Birchbark House, 2009)
Winner of the Scott O'Dell Award for Historical Fiction, The Game of Silence is the second novel in the critically acclaimed Birchbark House series by New York Times bestselling author Louise Erdrich. Her name is Omakayas, or Little Frog, because her first step was a hop, and she lives on an island in Lake Superior. One day in 1850, Omakayas's island is visited by a group of mysterious people. From them, she learns that the chimookomanag, or white people, want Omakayas and her people to leave their island and move farther west. That day, Omakayas realizes that something so valuable, so important that she never knew she had it in the first place, could be in danger: Her way of life. Her home. The Birchbark House Series is the story of one Ojibwe family's journey through one hundred years in America. The New York Times Book Review raved about The Game of Silence: "Erdrich has created a world, fictional but real: absorbing, funny, serious and convincingly human."